Wybrane problemy i dylematy społecznoekonomicznego wartościowania relacji człowiek - środowisko naturalne - Maciej Rudnicki (Studia Ecologiae et Bioethicae)
In this article autor shows the relation between human and natural environment and the chosen problems connected with this especially social, technological, economical with ecological and law problems and dilemmas connected with ecological safety of the human and the whole biosphere.